Intraoperative ICG-Fluorescence Imaging of Lymph Nodes in Robot-Assisted Radical Cystectomy in Patients with Bladder Cancer - V. N. Pavlov; M. F. Urmantsev; M. R. Bakeev (Креативная хирургия и онкология, 2023)
Introduction. Bladder cancer dominates among global health problems. Radical cystectomy is the recognized standard of care for muscle-invasive bladder cancer with bilateral pelvic lymphadenectomy as a mandatory step in the surgical procedure. The concept of sentinel lymph nodes, acting as a barrier to the spread of malignant process, can be beneficial in terms of reducing the extent of pelvic lymphadenectomy. Intraoperative imaging using indocyanine green now appears to be a contemporary and relevant method for intraoperative imaging of sentinel lymph nodes. Materials and methods. A study involving 28 patients diagnosed with bladder cancer was carried out at the clinic of the Bashkir State Medical University. All patients underwent robot-assisted radical cystectomy with intracorporeal formation of a heterotopic neobladder using Bricker technique. At the stage of pelvic lymphadenectomy, the isolated lymph nodes were evaluated and intraoperative ICG-fluorescence was performed. All lymph nodes obtained were examined microscopically and the results were interpreted taking into account the intraoperative diagnosis. Results and discussion. Intraoperative ICG fluorescence identified sentinel lymph nodes in 7 of 9 patients (77.8%, p < 0.05), with sensitivity equal to 77.8%, p < 0.05 and specificity — 87.5%, p < 0.05. Conclusion. The results proved a high reliability of the method of intraoperative lymph nodes imaging with indocyanine green in patients with muscle-invasive bladder cancer. Fluorescence navigation in cancer surgery opens up new opportunities for improving perioperative outcomes and reducing complications.